2018
DOI: 10.1111/efp.12442
|View full text |Cite
|
Sign up to set email alerts
|

In‐vitro antifungal activity of several biorational fungicides against Calonectria pseudonaviculata, the causal agent of Buxus hyrcana blight

Abstract: In recent years, the outbreak of box blight disease caused by Calonectria pseudonaviculata in Caspian Hyrcanian forests of Iran makes it necessary to find both efficient and environmentally friendly compounds as possible alternatives to currently available fungicides. Seven biorational compounds were tested for inhibitory activities against mycelial growth and conidial germination of C. pseudonaviculata Cy‐08 under in‐vitro conditions. Potassium sorbate and salicylic acid as organic compounds and copper (II) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…It could be suggested that the growth rate of this fungal isolate was affected by the acidity of the media, and these humic substances do not have antifungal properties. However, Yoldashkhan et al () studies showed that the growth of C. pseudonaviculata was pH‐independent, and this fungus could grow under both acidic and alkaline conditions (pH of 4–12). Therefore, it can be reasoned that effects of differing pHs on growth of C. pseudonaviculata were very minimal and that such humic substances do possess antifungal properties against the causal agent of boxwood blight disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It could be suggested that the growth rate of this fungal isolate was affected by the acidity of the media, and these humic substances do not have antifungal properties. However, Yoldashkhan et al () studies showed that the growth of C. pseudonaviculata was pH‐independent, and this fungus could grow under both acidic and alkaline conditions (pH of 4–12). Therefore, it can be reasoned that effects of differing pHs on growth of C. pseudonaviculata were very minimal and that such humic substances do possess antifungal properties against the causal agent of boxwood blight disease.…”
Section: Discussionmentioning
confidence: 99%
“…The radial growth of Cy‐08 mycelia was measured 30 days post‐inoculation when the negative control colony completely enriched the plate area. Inhibition percentage was assessed by the following formula (Yoldashkhan, Samavat, & Zamanizadeh, ):HGIfalse(%false)=1-colony diameter in treated platecolony diameter in the negative control plate×100…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation